A Prospective Trial on Reuse of Tissue Expanders - K Agrawal; K N Panda; A Agrawal (Indian Journal of Plastic Surgery)
A report on a prospective trial on the reuse of tissue expander is presented, to determine the feasibility of reusing these implants, the risks involved and the incidence of complications. Four tissue expanders of different capacities were repeatedly used in 17 patients for different indications, after explaining the possible risks to all of them. Two patients encountered complications while reusing the expanders, but this did not compromise the final result. We feel that like refurbished cardiac pacemakers, the reuse of these expanders has no untoward effect on the patient as well as on the reconstructive procedure. A protocol for expander removal, resterilization and testing has been described.